Awakening Solar Hydrogen Evolution of MoS2 in Alkalescent Electrolyte through Doping with Co. Issue 14 (18th June 2019) - Jia, Yulong; Wang, Zhonghao; Wang, Luyang; Ma, Ying; Wang, Guannan; Lin, Yinhe; Hu, Xun; Zhang, Kan
Abstract: Transition metal dichalcogenides, especially MoS2, have been regarded as promising cocatalysts for the hydrogen evolution reaction (HER) because of a near‐zero Gibbs free energy for H + absorption. However, the HER activity of MoS2 is profoundly restricted by acidic media. Co‐doped MoS2 (Co‐MoS2 ) nanosheets are found to enable the highly efficient solar H2 evolution of CdS nanowires (NWs) in alkalescent electrolyte. The content of Co in MoS2 is optimized to 2.8 % and the Co‐MoS2 content in Co‐MoS2 /CdS NWs hybrids is 2.5 wt %; the optimized Co‐MoS2 /CdS NWs shows a high H2 evolution rate of 14.22 mmol g −1 h −1 and 71 % apparent quantum efficiency in the Na2 SO3 electrolyte. Moreover, the H2 generation enabled by the Co‐MoS2 cocatalyst can exhibit universality in alkalescent electrolytes, such as triethanolamine (TEA) and disodium ethylenediaminetetraacetic acid (EDTA), exhibiting greater photocatalytic H2 generation than Pt/CdS. The design of Co‐MoS2 /CdS sheds light on the development of highly efficient low‐cost photocatalysts for solar H2 generation from water reduction. Abstract : Doped into action : MoS2 with a trigonal prismatic structure is most stable for the hydrogen evolution reaction but suffers from the acidic media. After doping with Co, enabling the capacity of solar H2 evolution in the alkalescent electrolyte, it was found that the H2 production rates in various alkalescent electrolytes are strongly dependent on the electronic energy level of hole scavengers.